Molecular Identification of Silver-Barb (Barbonymus sp.) Based on COI and Cyt-b gene region from East Java - Rahmawati, Mutiara; Mukti, Akhmad Taufiq; Andriyono, Sapto (Journal of Marine and Aquatic Sciences; Vol 8 No 1 (2022)DO - 10.24843/jmas.2022.v08.i01.p13, 2022)
This study aims to determine the genetic character of cyprinid fish (Barbonymus sp.) using the mtDNA gene in the COI and Cyt-b gene regions. Samples were collected from the various areas in East Java Province, including Gresik, Mojokerto, Madiun, Malang, and Banyuwangi. The caudal peduncle of the cyprinid fish was used for molecular identification. Isolation and purification of its genomic DNA using the gSYNCTM DNA Extraction kit. We used a polymerase chain reaction machine for template DNA amplification with COI primers, including FishF1 and FishR1, while Cyt-b primers, including GluDG-L and CB2-H. The results showed that all cyprinid fish sequences were successfully amplified with the COI gene of 648 bp and the Cyt b gene of 408 bp. The results of the BLASTN analysis show that there are two species of cyprinid fish that have been found, namely Barbonymus gonionotus and Barbonymus schwanenfeldii, with percentage identities ranging from 99-100%. The species Barbonymus gonionotus was found in five regions (Gresik, Mojokerto, Madiun, Malang, and Banyuwangi), while Barbonymus schwanenfeldii was only found in Malang. The genetic distance value based on the COI gene ranged from 0.00000-0.10694, while the genetic distance value based on the Cyt-b gene ranged from 0.00000-1.15662. Conservation status based on IUCN Red List data, the species Barbonymus gonionotus and Barbonymus schwanenfeldii are included in the Least Concern (LC) category, and these species, according to CITES data, have not been evaluated or Not Evaluated.